PENGEMBANGAN ALGORITMA PENGENALAN JENIS KALIMAT PADA BAHASA ARAB DENGAN METODE AFFIX MAPPING - Maksum Ro’is Adin Saf; Dini Hidayatul Qudsi; Istianah Muslim (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Arabic is one of the most popular languages in Indonesia which is Muslim population being majority. Ability to recognize the types of sentence in Arabic Language is one of basic topic in Arabic language studying. The type of sentence in Arabic is known from the first word in the sentence, but often the first word of a sentence is not the original words, so it can not be found directly in the dictionary. In this reseach, the Arabic Stemming algorithm was modified to find the type of the word using affixes include to the word, this method refers to the rules in Sharf science, therefore this method is named as Affix Mapping Algorithm. The algorithm that has been prepared is tested using Cyclomatic Complexity method and the result shows that the independent path obtained is 5, from the result it can be concluded that the algorithm is structured well, very easy to test, and last long.